Truck drivers and common sense in Brazilian society (Research, Society and Development, 2019)
In the first half 2018 there was a large strike of truck drivers in Brazil that affected the supply of fuel, food and other goods in most of the country. As consequence of the strike according to the Government, there were losses and subsequent increase of other fuels to compensate the losses with the decrease in the price of diesel. The common people have a perception regarding events and one of the ways to measure this is through the linguistic-discursive survey present in Web cartoons. The purpose of this article is to present a survey of the social representations obtained with the Web in relation to the strike of truck drivers. We did a qualitative social research. We verified that there is a general feeling regarding the importance of this modal of transport for the Country, the fuel prices are high for many truck drivers, there is manipulation on the part of the holders of the power and that the truck drivers represent a force that can influence the Country.